An assessment of maternal quality of life in the postpartum period in southern Brazil: a comparson of two questionnaires - Zubaran, Carlos (2009)
OBJECTIVES: To assess maternal quality of life (QoL) during the postpartum period and to compare the performance of two QoL questionnaires across a sample of 101 women in southern Brazil. To our knowledge, this is the first study that measures maternal quality of life during the postpartum period in Brazil. INTRODUCTION: There is limited information about postpartum maternal quality of life in Brazil. The are no Portuguese versions of instruments specifically designed to measure quality of life during the postpartum period. METHODS: Research participants completed the Portuguese version of the World Health Organization Quality of Life Assessment-Bref (WHOQOL-BREF) and Multicultural Quality of Life Index (MQLI) questionnaires. The correlations between the MQLI and the discrete areas of WHOQOL-BREF were examined using Pearson Product-Moment Correlation Coefficients. RESULTS: We report a significant correlation between the global MQLI and the four domains of the WHOQOL-BREF scores (p < 0.01). An analysis of variance revealed a significant difference in mean scores in the Psychological and Environment domains according to different socio-economic strata: F (3, 97) = 3.81, p = 0.012 and F (3, 97) = 4.03, p = 0.01, respectively. DISCUSSION: The WHOQOL-BREF questionnaire may be more sensitive than the MQLI in detecting the impact of socioeconomic status on the QoL of postpartum women. CONCLUSION: The sample of postpartum women evaluated in this study presented favorable QoL scores according to both the MQLI and WHOQOL-BREF questionnaires. Our results also indicate that the WHOQOL-BREF and the MQLI questionnaires have a significant correlation in terms of their assessments of postpartum mothers.